Va rog ajutatima:24-3•{[(18-11)•(63÷21)-2•(36-27)÷3]÷(32-29)-1}=
Răspunsuri la întrebare
Răspuns de
2
24-3•{[(18-11)•(63÷21)-2•(36-27)÷3]÷(32-29)-1}=
24-3•{[(18-11)•3-2•(36-27)÷3]÷(32-29)-1}=
24-3•[(7•3-2•9÷3)÷3-1]=
24-3•[(21-18÷3)÷3-1]=
24-3•[(21-6)÷3-1]=
24-3•(15÷3-1)=
24-3•(5-1)=
24-3•4=
24-12=12
24-3•{[(18-11)•3-2•(36-27)÷3]÷(32-29)-1}=
24-3•[(7•3-2•9÷3)÷3-1]=
24-3•[(21-18÷3)÷3-1]=
24-3•[(21-6)÷3-1]=
24-3•(15÷3-1)=
24-3•(5-1)=
24-3•4=
24-12=12
JustYou2oo:
Cu placere!
Răspuns de
0
24-3×[(7×3-2×9÷3)÷3-1]
24-3×[(21-18÷3)÷3-1]
24-3×[(21-6)÷3-1]
24-3×(15÷3-1)
24-3×(5-1)
24-3×4=24-12=12
Alte întrebări interesante
Fizică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Fizică,
9 ani în urmă